Avian Use of Agricultural Areas as Migration Stopover Sites: A Review of Crop Management Practices and Ecological Correlates - Blount, J. David; Horns, Joshua J.; Kittelberger, Kyle D.; Neate-Clegg, Montague H. C.; Şekercioğlu, Çağan Hakkı (Frontiers in Ecology and Evolution, 2021)
An estimated 17% of migratory bird species are threatened or near threatened with extinction. This represents an enormous potential loss of biodiversity and cost to human societies due to the economic benefits that birds provide through ecosystem services and ecotourism. Conservation of migratory bird species presents many unique challenges, as these birds rely on multiple geographically distinct habitats, including breeding grounds, nonbreeding grounds, and stopover sites during migration. In particular, stopover habitats are seldom studied relative to breeding and nonbreeding habitats, despite their importance as refueling stations for migratory birds. In this study, we summarize the current research on the use of temporary primary crops by birds during migration and we assess the species characteristics and agricultural practices most often associated with the use of cropland as stopover habitat. First, we conducted a systematic review of the literature to document the effects various farming practices and crop types have on the abundance and diversity of migratory birds using agricultural areas for stopovers. Second, we analyzed the ecological correlates of bird species in the Northern Hemisphere that predict which species may use these areas while migrating. We ran a GLMM to test whether primary diet, diet breadth, primary habitat, habitat breadth, or realm predicted stopover use of agricultural areas. Our review suggests that particular crop types (principally rice, corn, and sunflower), as well as farming practices that result in higher non-cultivated plant diversity, encourage the use of agricultural areas by migrating birds. We found that cropland is used as stopover habitat by bird species that can utilize a large breadth of habitats, as well as species with preferences for habitat similar in structure to agricultural areas.